2005
DOI: 10.1111/j.1399-3062.2005.000111.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection after autologous stem cell transplantation: incidence and outcome in a group of patients undergoing a surveillance program

Abstract: This study was performed to evaluate the incidence, risk factors, and outcome of cytomegalovirus (CMV) infection in autologous stem cell transplantation (ASCT), with the aim of performing preemptive therapy in patients with antigenemia. Starting from 2001, 171 consecutive ASCTs were performed in 136 patients; 102 of these patients were seropositive for CMV at the onset of hematological disease. In all these patients, a CMV pp65 antigenemia assay was determined weekly, starting from the day when the absolute ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
2
23
2
1
Order By: Relevance
“…The reported CMV reactivation rates among auto-SCT patients vary considerably, ranging from 4% for patients with CMV disease (10) and 13% for patients with viremia, viruria, and CMV disease combined (3) to 29% for patients with antigenemia (viremia) (20) and 39% for patients with antigenemia (5). The rate of 12% from this study was at the median.…”
Section: Discussionmentioning
confidence: 99%
“…The reported CMV reactivation rates among auto-SCT patients vary considerably, ranging from 4% for patients with CMV disease (10) and 13% for patients with viremia, viruria, and CMV disease combined (3) to 29% for patients with antigenemia (viremia) (20) and 39% for patients with antigenemia (5). The rate of 12% from this study was at the median.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of CMV infection/disease following ASCT, along with high rates of mortality primarily due to CMV pneumonia [2][3][4][5][6]. However, most of this information is from the era prior to novel chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, hematologic patients treated with high-dose chemotherapy and who underwent autologous stem cell transplantation (ASCT) were historically considered to have a low risk of CMV reactivation or end-organ disease. Previous studies on lymphoma and myeloma patients suggested an incidence of CMV reactivations of about 30%-40% when CMV determination was based on polymerase-chain reaction (PCR)/antigenemia prospective surveillance and of 1%-13% when determinations were performed only on the basis of clinical suspicion of infection, with a infection-mortality rate that ranged between 0% and 100% [2][3][4][5][6][7][8][9][10][11] . The guidelines of the European Conference on Infections in Leukemia (ECIL), published in 2008, consider the routine monitoring of CMV unnecessary in patients undergoing ASCT because of the low risk progression from infection to disease, with the exception of patients receiving CD34-selected grafts and prior treatment with Fludarabine, Cladribine or Alemtuzumab, considering that this setting of patients presented a profound alteration of T-cell-mediated immunity functional status [12] .…”
Section: Introductionmentioning
confidence: 99%